One-step rejuvenation for prolonging running lifespan of nanofiltration membranes - Guoyuan Pan; Muhua Zhao; Ying Wan; Guoke Zhao; Hao Yu; Gongqing Tang; Yang Zhang; Yiqun Liu (Advanced Membranes, 2024)
Commercial nanofiltration (NF) membranes based on polyamides may experience a decline in permeation performance after prolonged operation. The short lifespan of NF membranes will lead to waste and additional carbon emissions. Thus, rejuvenating membranes and extending their lifespan seem more meaningful than investigating new materials. In this paper, polyamide NF membranes were modified with various polyphenol monomers to improve their permeation performance. The effects of different polyphenols on pore size, surface morphology, and permeation performance of the NF membranes were thoroughly investigated. After modification with tannic acid, the NF membrane exhibits improved salt rejection while experiencing an acceptable decrease in water flux. It should be noted that the commercial NF membrane element fabricated by Koch can recover its Na2SO4 rejection from 83.0% to 94.2% and demonstrate long-term stability after rejuvenation with tannic acid. Combined with the environmental friendliness of polyphenols, this straightforward modification method has the potential for prolonging the operational lifespan of industrial NF membrane products.